Changes in denture teeth location in three different flasking techniques - Al-Ali, Ahmed Asim; Mohammed, Abdullah Jasim; Sheet, Omar Abdul Mohsen (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Artificial tooth movement may compromise the occlusion of complete (or implant-supported complete) over-dentures. This movement can lead to traumatic occlusion that may need to be corrected because the planned harmonious occlusion is lost, mainly when anatomic artificial teeth are utilized. Purpose: The study was conducted to evaluate the effect of the combination of gypsum plaster and laboratory silicon on the artificial teeth movement during the flasking procedure using radiographic imaging of intra-flask changes. Methods: In the current study, 90 identical mandibular complete dentures were fabricated and divided into two groups according to the acrylic material used. Stainless-steel pieces (0.5×0.5) were placed in the (buccal and mesiobuccal) cusp tips of the first premolar and first molar on both sides. Each group was subdivided into three subgroups (n=15) representing different techniques of flasking. Radiographs were taken at three phases of the flasking procedure, before and after the second investment layer and after curing the acrylic. The anteroposterior and mediolateral factors were calculated, and the data were analyzed by the one-way analysis of variance (ANOVA) and Duncan’s post hoc tests at P˂0.05. Results: The anteroposterior factors of the groups had insignificant differences at all phases, and the mediolateral factors showed significant differences in the gypsum samples and total silicon samples. Conclusion: Anteroposterior movement of the artificial teeth was not changed due to bracing between the teeth, and a mixed silicon and plaster investing layer had the smallest teeth location changes during the packing and curing phases.